USM, IIUM SIGN MOU TO SPEARHEAD GLOBAL HALAL RESEARCH AND SERVICES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, December 2015 – Universiti Sains Malaysia (USM) and International Islamic University Malaysia (IIUM) signed a Memorandum of Understanding (MoU) to spearhead the initiative to collaborate in research and services related to global syariah compliance and halal certification.